2017
DOI: 10.1007/s11239-017-1557-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after inferior vena cava filter placement in cancer patients diagnosed with pulmonary embolism: risk for recurrent venous thromboembolism

Abstract: Venous thromboembolism (VTE) is a common complication in cancer patients and anticoagulation (AC) remains the standard of care for treatment. Inferior vena cava (IVC) filters may also used to reduce the risk of pulmonary embolism, either alone or in addition to AC. Although widely used, data are limited on the safety and efficacy of IVC filters in cancer patients. We performed a retrospective review of outcomes after IVC filter insertion in a database of 1270 consecutive patients with cancer-associated pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Out of 1270 patients diagnosed with a PE over a one-year period, 317 received an IVCF; however, the indication for insertion was unclear in 23%. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Out of 1270 patients diagnosed with a PE over a one-year period, 317 received an IVCF; however, the indication for insertion was unclear in 23%. 13 …”
Section: Discussionmentioning
confidence: 99%
“…While some studies suggested that IVCFs are safe and effective, others found an increased risk of recurrent deep venous thrombosis (DVT; indeed, the cancer-related hypercoagulability is not corrected by the IVCF), as well as no benefit regarding pulmonary embolism (PE) incidence or short-term mortality. [34][35][36][37][38][39][40] Nevertheless, most guidelines recommend the use of IVCF in cancer patients with proximal acute DVT or PE when anticoagulant therapy is contraindicated. [41][42][43][44] Such is the case of major surgery or invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…• Results from studies on the use of IVCF in cancer patients with VTE are controversial. [34][35][36][37][38][39][40] • Consensus exists on its use in patients with PE or DVT when ACG is contraindicated, especially in the first weeks after VTE. [41][42][43][44] • Concern about early and delayed adverse effects associated with IVCF is increasingly growing.…”
mentioning
confidence: 99%
“…The retrievable IVC filter is a commonly used vascular device intended to prevent life-threatening pulmonary emboli, but its effectiveness is not well established. 3 Although many data underscore the efficacy and need of the IVC filter, FDG PET/CT images of the presented cases have illustrated effective capture of the IVC thrombi by the filters.…”
mentioning
confidence: 83%